Neutrino - Nucleus Reaction Cross Sections at Low and Intermediate Energies - Kosmas, T. S.; Oset, E. (HNPS Advances in Nuclear Physics, 2020)
Neutrino-nucleus reactions at low and intermediate energies up to Ev=500 MeV are investigated for the most interesting nuclei from an experimental point of view. We mainly focus on calculations of neutrino-nucleus cross sections for semi-inclusive processes, for which recent measurements from radiochemical experiments at LAMPF and KARMEN have been obtained. Inclusive cross sections are also calculated and discussed. The method employed uses the Lindhard function for the description of the particle-hole excitations of the final nucleus via a local density approximation.